Self-heating particle and preparation method thereof, self-heating agent, self-heating device and application
By mixing the metal negative electrode material, positive electrode material and binder in a specific proportion to make a granular material, and contacting it with alkaline electrolyte, the metal air oxidation reaction exothermic heat release is solved, and the traditional self-heating materials are slow to rise, violent reaction and difficult to control the temperature, and the effect of rapid heating, controllable temperature and safeness is achieved.
Patent Information
- Application Number
- CN202411807072.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional self-heating materials have problems such as slow temperature rise, severe reaction and difficult to control the temperature, and there are safety risks in storage and use.
By mixing the metal negative electrode material, positive electrode material and binder in a specific proportion to make a granular material and contacting it with the alkaline electrolyte, the metal air oxidation reaction exothermic heat, and rapid and controllable heating is achieved.
It achieves the effect of rapid heating, controllable temperature, and lasting heating time, and is safer to store and use, and is suitable for applications in various fields.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of self-heating materials, and in particular to a self-heating particle and a preparation method thereof, a self-heating agent, a self-heating device and applications thereof. Background Art
[0002] Self-heating technology originated from the development of self-heating food for individual soldiers to meet the needs of military field operations. Self-heating materials are the core components of self-heating devices. Self-heating materials refer to materials that can generate heat through chemical reactions or physical processes; among them, chemical reaction type self-heating materials are the most common. Chemical heating agents can produce chemical reactions and release heat when exposed to specific conditions (such as air, moisture or other chemicals).
[0003] The earliest self-heating technology put into use was the hydration reaction of quicklime. The exothermic principle is that heat is released during the reaction of CaO and H2O to generate Ca(OH)2, and no harmful gases are produced during the reaction. However, it has disadvantages such as low heat release per unit mass of heating agent, heating packs are easily affected by moisture, and have a short shelf life. Therefore, this type of self-heating material has been gradually eliminated.
[0004] At present, self-heating materials have been widely used in the fields of self-heating food and medical care and beauty. Commonly used self-heating materials include aluminum-based self-heating agents, magnesium-based self-heating agents and iron-based self-heating agents; the principle is that when micro-nano-scale metal Al or Mg particles come into contact with water, a hydration reaction occurs on their surface to generate hydroxides with a loose porous structure, releasing heat; but the reaction products include hydrogen, which poses a safety hazard. The oxidation reaction rate of iron under natural conditions is slow. Using water, inorganic salts, activated carbon and iron powder to form a primary battery can speed up the oxidation reaction and convert chemical energy into thermal energy; however, the heating temperature of this type of heating agent is low and usually cannot meet the needs of heating food and drinks.
[0005] Self-heating materials can also release heat by utilizing the exothermic principle of metal oxidation reactions. The oxides of metal materials such as Fe mostly present a loose porous structure, which is suitable for continuous heat release in oxidation reactions. The reaction releases less heat per unit time. In order to obtain a large amount of continuous heat energy, the metal needs to be ultra-finely processed. The high specific surface area of micron or even nano-scale metal powders can accelerate the reaction rate, thereby reaching a higher temperature. However, metals such as Mg and Al are not suitable for exothermic metal oxidation reactions. When they come into contact with oxygen, they will quickly produce a dense oxide film on the surface, which prevents subsequent reactions from occurring and makes it difficult to continuously release heat.
[0006] The exothermic principles of the self-heating materials commonly used at present include aluminum thermite reaction, iron oxygen absorption corrosion oxidation exothermicity, redox exothermicity, aluminum water reaction exothermicity, magnesium water reaction exothermicity, etc.; however, the self-heating materials based on the above reaction exothermic principles have the disadvantages of slow heating, violent reaction and difficult temperature control.
[0007] Therefore, traditional self-heating materials still need to be further improved. Summary of the invention
[0008] Based on this, one or more embodiments of the present application provide a self-heating particle that is easy to use, generates heat quickly, and has controllable temperature, as well as a preparation method, a self-heating agent, a self-heating device, and an application thereof.
[0009] According to a first aspect of an embodiment of the present application, a self-heating particle is provided, wherein the self-heating particle comprises a metal negative electrode material, a positive electrode material and a binder mixed with each other;
[0010] Wherein, the mass ratio of the metal negative electrode material, the positive electrode material and the binder is (35~55):(10~20):(1~10).
[0011] In one embodiment, the particle size of the self-heating particles is 0.15 mm to 1.4 mm.
[0012] In one embodiment, the positive electrode material includes a carbon material;
[0013] Optionally, the carbon material includes one or more of activated carbon, graphite, expanded graphite, carbon nanotubes and graphene.
[0014] In one embodiment, the positive electrode material further includes a catalyst;
[0015] Optionally, the catalyst includes one or more of noble metals and alloys thereof, transition metal oxides, transition metal sulfides, functionalized carbon materials and metal nitrides.
[0016] In one of the embodiments, the mass ratio of the carbon material to the catalyst is (90~100):(0~10).
[0017] In one embodiment, the metal negative electrode material includes one or more of aluminum, magnesium, zinc and iron.
[0018] In one embodiment, based on the total weight of the metal negative electrode material, the mass percentage of the aluminum is 80% to 100%, and the sum of the mass percentages of the magnesium, the zinc and the iron is 0 to 20%.
[0019] In one embodiment, the binder includes one or more of polyethylene glycol, polytetrafluoroethylene, potassium polyacrylate, sodium polyacrylate, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, propylene glycol, glycerol, ethanol and water.
[0020] In one embodiment, based on the total weight of the binder, the sum of the mass percentages of the carboxymethyl cellulose and the sodium carboxymethyl cellulose is 18% to 22%.
[0021] A method for preparing the above-mentioned self-heating particles comprises the following steps:
[0022] Evenly mixing the metal negative electrode material, the positive electrode material and the binder to obtain a mixture;
[0023] The mixture is sequentially subjected to extrusion granulation, drying and screening to obtain self-heating particles.
[0024] A self-heating agent comprises an alkaline electrolyte and the self-heating particles mentioned above, wherein the alkaline electrolyte and the self-heating particles are placed separately.
[0025] In one embodiment, the mass ratio of the metal negative electrode material, the positive electrode material, the binder and the alkaline electrolyte is (35~55):(10~20):(1~10):(35~55).
[0026] In one embodiment, the alkaline electrolyte includes one or more of potassium hydroxide and its hydrate, sodium hydroxide and its hydrate, lithium hydroxide and its hydrate, calcium hydroxide and its hydrate, potassium carbonate and its hydrate, sodium carbonate and its hydrate, lithium carbonate and its hydrate, calcium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate.
[0027] In one embodiment, based on the total weight of the alkaline electrolyte, the sum of the mass percentages of the potassium hydroxide and its hydrate and the sodium hydroxide and its hydrate is 80% to 100%, and the sum of the mass percentages of the sodium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate is 0 to 20%.
[0028] A self-heating device comprises the self-heating agent mentioned above.
[0029] A method for applying the self-heating device is to contact an alkaline electrolyte with the self-heating particles.
[0030] Compared with the traditional technology, this application has the following beneficial effects:
[0031] The present application mixes metal negative electrode materials and positive electrode materials in a specific ratio to form a granular material with positive and negative short circuits. When used, it is contacted with an alkaline electrolyte to rapidly undergo a metal-air oxidation reaction, which has the advantages of rapid heating, controllable temperature, and long-lasting heating time. In addition, the self-heating particles of the present application do not need to be isolated from the air during storage, making storage more convenient; during the reaction, no external water and high-temperature triggering conditions are required, no dangerous products are generated, and the safety risk is low, making it suitable for promotion and application in a variety of fields. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0034] At present, the heat release principle of commonly used self-heating devices includes thermite reaction, which can release a large amount of heat through the replacement reaction between aluminum and metal oxides. However, thermite reaction requires high temperature to trigger, and the heat release is violent after the reaction is started, making it difficult to control the temperature.
[0035] Traditional technology records the preparation method of Al-KMnO4-MnO2 and Fe-KMnO4-MnO2 self-heating materials, which use the redox reaction of KMnO4 on Al or Fe to release heat. The self-heating material does not need to be strictly sealed when the material is stored, but an appropriate amount of water needs to be added when it is used, and the self-heating material will react exothermically. The temperature of Al-KMnO4-MnO2 self-heating material and Fe-KMnO4-MnO2 reaches the maximum temperature of 150°C and 100°C respectively from the room temperature of 25°C within 10 minutes. However, KMnO4 is a strong oxidant and there are safety risks in its use.
[0036] Traditional technology records the self-heating material of porous iron nanoparticles with a high specific surface area, which uses the oxidation reaction of iron with air to generate heat. However, this method is complex and has harsh material storage conditions. It requires the dispersion, slurrying, molding, and drying of nano-iron oxide and ceramic matrix, sintering at above 1000°C, and high-temperature reduction in hydrogen atmosphere to obtain nano-iron ceramic composite materials. When storing, it needs to be strictly isolated from the air and stored in an inert gas or vacuum.
[0037] The traditional aluminum-based self-heating device at extremely low temperatures uses a two-step method to achieve heat release. First, the alkaline antifreeze reacts with the aluminum powder, iron powder, magnesium powder, etc. in the low-temperature heating agent to produce high-temperature hot spots, and then external water is added to start the aluminum-water reaction and continue to release heat. The heat release per unit mass of metal in the aluminum-water reaction, magnesium-water reaction, and thermite reaction is large, but the reaction itself requires high temperature. Bulk pure aluminum needs to be at a high temperature of about 1000°C to react with water vapor. Aluminum powder below the micron level also requires reaction conditions above 50°C to react violently. The conditions for thermite reaction are mainly high-temperature ignition above 1000°C, so it needs to be stimulated by high temperatures generated by other exothermic reactions. Such reactions are often violently exothermic and difficult to control, and these factors will lead to complex structures of self-heating devices and low heat utilization efficiency.
[0038] The traditional multi-step method realizes the exothermic self-heating device. First, potassium permanganate reacts with propylene glycol or propylene glycol to produce oxidation reaction, and calcium oxide reacts with hydration reaction to generate heat and increase the temperature. Then, aluminum powder reacts with ferric oxide powder, ferroferric oxide powder, silicon dioxide powder and manganese dioxide powder to release a large amount of heat. Specifically, the multi-step method first preheats the self-heating device through a reaction that is easy to react and exothermic, and then triggers the self-heating reaction that needs high temperature to start to achieve the heating purpose, resulting in a complex self-heating device and unstable self-heating performance.
[0039] Based on this, the first aspect of the present application provides a self-heating particle, including a metal negative electrode material, a positive electrode material and a binder mixed with each other;
[0040] Among them, the mass ratio of metal negative electrode material, positive electrode material, binder and alkaline electrolyte is (35~55):(10~20):(1~10):(35~55).
[0041] The present application is based on the principle of heat release due to internal short circuit of metal-air battery. The metal negative electrode material and the positive electrode material are mixed to form a granular material with positive and negative electrode short circuit. When the granular material is contacted or mixed with an alkaline electrolyte, a metal-air oxidation reaction and heat release can occur rapidly.
[0042] If the self-heating particles need to be stored for a long time, moisture-proof measures must be taken.
[0043] Understandably, after the metal negative electrode material, positive electrode material and binder are made into particles, the risk of human body inhaling powder can be reduced.
[0044] In some specific embodiments, the mass ratio of the metal negative electrode material, the positive electrode material and the binder is (38-42):(14-16):(4-6). Controlling the mass ratio of the metal negative electrode material, the positive electrode material and the binder within the above-mentioned specific range can make the self-heating particles heat up faster when in contact with the electrolyte, reach a higher heating temperature, and maintain a temperature above 100°C for a longer time.
[0045] In an optional example, the mass ratio of the metal negative electrode material, the positive electrode material and the binder is 40:15:5.
[0046] In some embodiments, the particle size of the self-heating particles is 0.15 mm to 4 mm.
[0047] Optionally, the particle size of the self-heating particles is 0.18 mm to 1 mm.
[0048] Further optionally, the particle size of the self-heating particles is 0.25 mm to 0.5 mm.
[0049] In some embodiments, the positive electrode material includes a carbon material.
[0050] In some specific embodiments, the carbon material includes one or more of activated carbon, graphite, expanded graphite, carbon nanotubes, and graphene.
[0051] In some specific embodiments, the carbon material is selected from activated carbon.
[0052] In some embodiments, the positive electrode material further includes a catalyst.
[0053] In some specific embodiments, the catalyst includes one or more of noble metals and alloys thereof, transition metal oxides, transition metal sulfides, functionalized carbon materials, and metal nitrides.
[0054] In some embodiments, the catalyst is selected from manganese dioxide powder.
[0055] In some embodiments, the mass ratio of the carbon material to the catalyst is (90-100):(0-10). As an example, the mass ratio of the carbon material to the catalyst can be, but is not limited to, 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, 99:1 or 100:0.
[0056] In some embodiments, the metal negative electrode material includes one or more of aluminum, magnesium, zinc and iron.
[0057] In some specific embodiments, the metal negative electrode material is selected from aluminum. When aluminum is used as the negative electrode material, the negative electrode reaction is Al+4OH - →Al(OH)4 - +3e - ; The positive electrode reaction is O2+2H2O+4e - →4OH - The total reaction is 4Al+3O2+6H2O→4Al(OH)3 (△H=-31.72kJ / g). This reaction can occur at room temperature. The oxygen in the air is adsorbed by activated carbon to form the "positive electrode site" of the primary battery. After adding inorganic electrolyte, it will form several micro short-circuit points with the "negative electrode site" of the metal powder, and the reaction rate will increase. The presence of alkaline electrolyte can greatly reduce the activation energy of the reaction and increase OH - The conduction rate of ions can further improve the reaction efficiency.
[0058] The heat release per unit mass of the aluminum-air battery reaction is relatively high (-31.72 kJ / g), which is about 4.5 times that of the iron oxygen absorption corrosion reaction (-7.06 kJ / g), and about twice that of the aluminum-water reaction (-15.83 kJ / g) and the aluminum thermite reaction (-15.43 kJ / g); and the reaction products are environmentally friendly and pollution-free.
[0059] In some specific embodiments, the metal negative electrode material is selected from aluminum and magnesium.
[0060] In some of the embodiments, based on the total weight of the metal negative electrode material, the mass percentage of aluminum is 80% to 100%, and the sum of the mass percentages of magnesium, zinc and iron is 0 to 20%.
[0061] As an example, the mass percentage of aluminum can be, but is not limited to, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%; the sum of the mass percentages of magnesium, zinc and iron can be, but is not limited to, 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 5%, 16%, 17%, 18%, 19% or 20%.
[0062] In some embodiments, the binder includes one or more of polyethylene glycol, polytetrafluoroethylene, potassium polyacrylate, sodium polyacrylate, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, propylene glycol, glycerol, ethanol and water.
[0063] In some specific embodiments, the binder is selected from an aqueous solution of potassium polyacrylate.
[0064] In some specific embodiments, the binder is selected from an aqueous solution of potassium polyacrylate and sodium carboxymethyl cellulose.
[0065] In some embodiments, the sum of the mass percentages of carboxymethyl cellulose and sodium carboxymethyl cellulose is 18% to 22% based on the total weight of the binder. As an example, the sum of the mass percentages of carboxymethyl cellulose and sodium carboxymethyl cellulose can be, but is not limited to, specific values such as 18%, 19%, 20%, 21% or 22%.
[0066] By adjusting the types and proportions of metal negative electrode materials, positive electrode materials and binders, the heating rate and maximum temperature of self-heating products can be effectively improved, and the duration of high temperatures above 100°C can be extended. The temperature can also be controlled to reduce the risk of combustion and explosion.
[0067] The second aspect of the present application provides a method for preparing the self-heating particles of the first aspect, comprising steps S10 to S20.
[0068] Step S10: Evenly mix the metal negative electrode material, the positive electrode material and the binder to obtain a mixture.
[0069] Step S20: sequentially perform extrusion granulation, drying and screening on the mixture to obtain self-heating particles.
[0070] By granulating the mixture, the reaction can be controlled, the risk of combustion and explosion can be reduced, and safety can be improved.
[0071] In some specific embodiments, the drying temperature in step S20 is 50° C. to 60° C. As an example, the drying temperature may be, but is not limited to, specific values such as 50° C., 51° C., 52° C., 53° C., 54° C., 55° C., 56° C., 57° C., 58° C., 59° C. or 60° C.
[0072] The preparation method of the self-heating particles of the present application has the advantages of simple process and safety.
[0073] A third aspect of the present application provides a self-heating agent, comprising an alkaline electrolyte and the self-heating particles of the first aspect, wherein the alkaline electrolyte and the self-heating particles are placed separately.
[0074] The self-heating agent of the present application does not require the addition of exogenous water or the provision of high-temperature triggering conditions, and has the advantages of being easy to use.
[0075] The self-heating particles and alkaline electrolyte in the self-heating agent can be placed separately without being sealed. For example, the two can be packaged separately and placed in different containers, or they can be placed in the same container with an isolation chamber, as long as the two cannot directly contact each other.
[0076] In some embodiments, the alkaline electrolyte includes one or more of potassium hydroxide and its hydrates, sodium hydroxide and its hydrates, lithium hydroxide and its hydrates, calcium hydroxide and its hydrates, potassium carbonate and its hydrates, sodium carbonate and its hydrates, lithium carbonate and its hydrates, calcium carbonate and its hydrates, potassium bicarbonate and its hydrates, sodium bicarbonate and its hydrates, lithium bicarbonate and its hydrates, and calcium bicarbonate and its hydrates.
[0077] In some specific embodiments, the alkaline electrolyte may be in the form of flakes, particles, or powder.
[0078] In some of the embodiments, based on the total weight of the alkaline electrolyte, the sum of the mass percentages of potassium hydroxide and its hydrate and sodium hydroxide and its hydrate is 80% to 100%, and the sum of the mass percentages of sodium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate is 0 to 20%.
[0079] As an example, the sum of the mass percentages of potassium hydroxide and its hydrate and sodium hydroxide and its hydrate can be, but is not limited to, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100% or other specific values; the sum of the mass percentages of sodium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate can be, but is not limited to, 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 5%, 16%, 17%, 18%, 19% or 20% or other specific values.
[0080] In some specific embodiments, the alkaline electrolyte is selected from sodium hydroxide and sodium bicarbonate hydrate.
[0081] In some of the embodiments, the mass ratio of the metal negative electrode material, the positive electrode material, the binder and the alkaline electrolyte is (35~55):(10~20):(1~10):(35~55).
[0082] In an optional example, the mass ratio of the metal negative electrode material, the positive electrode material, the binder and the alkaline electrolyte is 40:15:5:40.
[0083] A fourth aspect of the present application provides a self-heating device, comprising the self-heating agent of the third aspect.
[0084] The self-heating device of the present application has the advantages of easy use, rapid heating, and controllable temperature, and can be applied to self-heating food, battery management, new tobacco, and military fields, etc.
[0085] A fifth aspect of the present application provides an application method of the above-mentioned self-heating device, which brings an alkaline electrolyte into contact with the self-heating particles.
[0086] The self-heating device of the present application does not require the provision of external water and high-temperature triggering conditions, does not generate hazardous products, has low safety risks, and is suitable for promotion and application in a variety of fields.
[0087] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0088] It should be noted that the parts of each substance in the examples of the present application refer to parts by weight.
[0089] Example 1
[0090] (1) 40 parts of aluminum powder with a particle size of less than 400 mesh and 15 parts of activated carbon with a particle size of less than 325 mesh are fully mixed; then 5 parts of potassium polyacrylate aqueous solution are added, and after fully mixing, extrusion granulation is performed, dried at 50°C, and crushed and sieved to obtain self-heating particles with a particle size greater than or equal to 0.25 mm and less than 0.5 mm.
[0091] (2) The self-heating particles prepared above are brought into contact with 40 parts of sodium hydroxide particles, and a short-circuit reaction of the metal-air battery occurs, releasing heat.
[0092] Example 2
[0093] The present invention is basically the same as Example 1, except that the particle size of the self-heating particles is greater than or equal to 0.15 mm and less than 0.25 mm.
[0094] Example 3
[0095] The method is basically the same as Example 1, except that the particle size of the self-heating particles is greater than or equal to 0.5 mm and less than 1 mm.
[0096] Example 4
[0097] The present invention is basically the same as Example 1, except that the particle size of the self-heating particles is greater than or equal to 1 mm and less than 1.4 mm.
[0098] Example 5
[0099] It is basically the same as Example 1, except that the weight proportion of aluminum powder is 45 parts and the weight proportion of sodium hydroxide is 35 parts.
[0100] Example 6
[0101] It is basically the same as Example 1, except that the weight parts of aluminum powder are 35 parts and the weight parts of sodium hydroxide are 45 parts.
[0102] Example 7
[0103] The method is basically the same as Example 1, except that an equal amount of polytetrafluoroethylene ethanol solution is used to replace the potassium polyacrylate aqueous solution.
[0104] Example 8
[0105] The method is basically the same as Example 1, except that an equal amount of polyethylene glycol 200 aqueous solution is used to replace the potassium polyacrylate aqueous solution.
[0106] Example 9
[0107] The method is substantially the same as Example 1, except that a mixture of 4 parts of potassium polyacrylate solution and 1 part of sodium carboxymethyl cellulose aqueous solution is used to replace 5 parts of potassium polyacrylate aqueous solution.
[0108] Example 10
[0109] The method is substantially the same as Example 9, except that a mixture of 32 parts of sodium hydroxide particles and 8 parts of sodium carbonate decahydrate crystals (Na2CO3•10H2O) is used instead of 40 parts of sodium hydroxide particles.
[0110] Embodiment 11
[0111] The method is basically the same as Example 9, except that an equal amount of sodium carbonate decahydrate crystals (Na2CO3•10H2O) is used to replace the sodium hydroxide particles.
[0112] Example 12
[0113] The method is substantially the same as Example 9, except that a mixture of 38 parts of sodium hydroxide particles and 2 parts of sodium carbonate decahydrate crystals (Na2CO3•10H2O) is used instead of 40 parts of sodium hydroxide particles.
[0114] Example 13
[0115] The method is substantially the same as Example 9, except that a mixture of 36 parts of sodium hydroxide particles and 4 parts of sodium carbonate decahydrate crystals (Na2CO3•10H2O) is used instead of 40 parts of sodium hydroxide particles.
[0116] Embodiment 14
[0117] The method is substantially the same as Example 9, except that a mixture of 28 parts of sodium hydroxide particles and 12 parts of sodium carbonate decahydrate crystals (Na2CO3•10H2O) is used instead of 40 parts of sodium hydroxide particles.
[0118] Embodiment 15
[0119] The method is substantially the same as Example 9, except that a mixture of 24 parts of sodium hydroxide particles and 16 parts of sodium carbonate decahydrate crystals (Na2CO3•10H2O) is used instead of 40 parts of sodium hydroxide particles.
[0120] Example 16
[0121] The method is basically the same as Example 9, except that an equal amount of potassium hydroxide particles are used to replace the sodium hydroxide particles.
[0122] Embodiment 17
[0123] The method is substantially the same as Example 10, except that a mixture of 14 parts of activated carbon and 1 part of manganese dioxide is used instead of 15 parts of activated carbon.
[0124] Embodiment 18
[0125] Basically the same as Example 17, except that a mixture of 38 parts of aluminum powder and 2 parts of magnesium powder is used to replace 40 parts of aluminum powder.
[0126] Embodiment 19
[0127] Basically the same as Example 17, except that a mixture of 36 parts of aluminum powder and 4 parts of magnesium powder is used to replace 40 parts of aluminum powder.
[0128] Embodiment 20
[0129] Basically the same as Example 17, except that a mixture of 32 parts of aluminum powder and 8 parts of magnesium powder is used to replace 40 parts of aluminum powder.
[0130] Embodiment 21
[0131] Basically the same as Example 19, except that a mixture of 14 parts of graphite and 1 part of manganese dioxide is used instead of a mixture of 14 parts of activated carbon and 1 part of manganese dioxide.
[0132] Embodiment 22
[0133] The method is substantially the same as Example 19, except that a mixture of 14 parts of expanded graphite and 1 part of manganese dioxide is used instead of a mixture of 14 parts of activated carbon and 1 part of manganese dioxide.
[0134] Comparative Example 1
[0135] 50 parts of aluminum powder with a particle size of 400 meshes were directly and evenly mixed with 50 parts of sodium hydroxide particles to produce a hydrogen evolution reaction.
[0136] Comparative Example 2
[0137] After 40 parts of aluminum powder with a particle size of 400 mesh and 15 parts of activated carbon with a particle size of 325 mesh are uniformly mixed, they are brought into contact with 45 parts of sodium hydroxide particles to generate intense heat.
[0138] Comparative Example 3
[0139] 40 parts of iron powder with a particle size of 400 mesh and 15 parts of activated carbon with a particle size of 325 mesh are uniformly mixed and then contacted with 45 parts of sodium hydroxide particles to release heat.
[0140] Comparative Example 4
[0141] The method is basically the same as Example 1, except that an equal amount of malic acid powder is used to replace the sodium hydroxide particles.
[0142] The types and weight proportions of the raw materials in the above-mentioned Examples 1-22 and Comparative Examples 1-4 are shown in Table 1.
[0143] Table 1
[0144]
[0145]
[0146] Performance Evaluation
[0147] Under the environmental condition of 26°C, the self-heating particles were placed in a glass chromatographic bottle with a mouth diameter of 8 mm, a volume of about 4 mL, and a bottle cap attached; the bottle cap was punched and an ultrafine thermocouple was inserted; alkaline electrolyte particles were added and the bottle cap was screwed on; the thermocouple was connected to a temperature sensor to record the temperature change in real time. The heating conditions of the self-heating materials of each embodiment and comparative example are shown in Table 2. The total weight of the self-heating particles and the alkaline electrolyte is 0.3 g.
[0148] Table 2
[0149]
[0150] From Examples 1 to 4, it can be seen that the smaller the particle size of the self-heating particles, the faster the heating speed and the higher the maximum temperature that can be reached; but it may affect the duration of the high temperature. When the particle size of the self-heating particles is between 0.25mm and 0.5mm, it can increase the temperature quickly and maintain the high temperature for a longer time.
[0151] It can be seen from Examples 1, 5 to 6 that when the mass ratio of the metal negative electrode material, the positive electrode material, the binder and the alkaline electrolyte is 40:15:5:40, the heating rate of the self-heating agent is the fastest and the high temperature is maintained for a longer time.
[0152] It can be seen from Examples 1, 7 to 9 that the self-heating material prepared by using potassium polyacrylate water as a binder has a significantly higher heating rate and high temperature duration effect than other types of binders; therefore, potassium polyacrylate water is preferably used as a binder. At the same time, adding a specific amount of carboxymethyl cellulose or sodium carboxymethyl cellulose to potassium polyacrylate water can further improve the heating rate and high temperature duration of the self-heating agent.
[0153] It can be seen from Examples 9 to 16 that mixing a strong alkaline electrolyte (such as potassium hydroxide, sodium hydroxide) with an aqueous weak alkaline electrolyte such as aqueous sodium carbonate in a specific ratio to prepare alkaline electrolyte particles can effectively increase the duration of high temperature above 100°C.
[0154] It can be seen from Example 10 and Example 17 that adding a specific mass fraction of catalyst to the positive electrode material can effectively accelerate the heating rate, increase the maximum temperature and prolong the high temperature maintenance time.
[0155] It can be seen from Examples 19, 21-22 that the self-heating material prepared by using activated carbon as the positive electrode material has a heating rate, maximum temperature and high temperature duration effect that are better than other types of positive electrode materials; therefore, activated carbon is preferred as the positive electrode material.
[0156] It can be seen from Examples 17 to 20 that the self-heating material prepared by mixing aluminum powder with a small amount of magnesium powder as the negative electrode material has a better heating rate, maximum temperature and high temperature duration effect than aluminum powder alone as the negative electrode material.
[0157] In Comparative Example 2, the instantaneous temperature rises to 309° C. within 5 seconds after the powders are evenly mixed. The heat release is difficult to control and there is a risk of explosion. Therefore, the powders need to be molded to improve safety.
[0158] In Comparative Example 3, after the iron powder, activated carbon and sodium hydroxide were directly mixed, the maximum temperature only rose to 52.1°C, which was far lower than the heating temperature of aluminum powder molding.
[0159] In Comparative Example 4, after the self-heating particles are mixed with the acidic electrolyte, the maximum heating temperature is only 32.4°C, which is too low to meet the usage requirements.
[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A self-heating particle, characterized in that: The self-heating particles include a metal negative electrode material, a positive electrode material and a binder mixed with each other; Wherein, the mass ratio of the metal negative electrode material, the positive electrode material and the binder is (35~55):(10~20):(1~10).
2. The self-heating particles according to claim 1, characterized in that: The particle size of the self-heating particles is 0.15 mm to 1.4 mm.
3. The self-heating particles according to claim 1, characterized in that: The positive electrode material includes a carbon material; Optionally, the carbon material includes one or more of activated carbon, graphite, expanded graphite, carbon nanotubes and graphene.
4. The self-heating particles according to claim 3, characterized in that: The positive electrode material also includes a catalyst; Optionally, the catalyst includes one or more of noble metals and alloys thereof, transition metal oxides, transition metal sulfides, functionalized carbon materials and metal nitrides.
5. The self-heating particles according to claim 4, characterized in that: The mass ratio of the carbon material to the catalyst is (90-100):(0-10).
6. The self-heating particle according to any one of claims 1 to 5, characterized in that: The metal negative electrode material includes one or more of aluminum, magnesium, zinc and iron.
7. The self-heating particles according to claim 6, characterized in that: Based on the total weight of the metal negative electrode material, the mass percentage of the aluminum is 80% to 100%, and the sum of the mass percentages of the magnesium, the zinc and the iron is 0 to 20%.
8. The self-heating particle according to any one of claims 1 to 5 and 7, characterized in that: The binder includes one or more of polyethylene glycol, polytetrafluoroethylene, potassium polyacrylate, sodium polyacrylate, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyvinyl alcohol, propylene glycol, glycerol, ethanol and water.
9. The self-heating particles according to claim 8, characterized in that: Based on the total weight of the binder, the sum of the mass percentages of the carboxymethyl cellulose and the sodium carboxymethyl cellulose is 18% to 22%.
10. The method for preparing the self-heating particles according to any one of claims 1 to 9, characterized in that: The steps include: Mixing the metal negative electrode material, the positive electrode material and the binder uniformly to obtain a mixture; The mixture is sequentially subjected to extrusion granulation, drying and screening to obtain self-heating particles.
11. A self-heating agent, characterized in that: The invention comprises an alkaline electrolyte and the self-heating particles according to any one of claims 1 to 9, wherein the alkaline electrolyte is placed separately from the self-heating particles.
12. The self-heating agent according to claim 11, characterized in that The mass ratio of the metal negative electrode material, the positive electrode material, the binder and the alkaline electrolyte is (35~55):(10~20):(1~10):(35~55).
13. The self-heating agent according to any one of claims 11 to 12, characterized in that: The alkaline electrolyte includes one or more of potassium hydroxide and its hydrate, sodium hydroxide and its hydrate, lithium hydroxide and its hydrate, calcium hydroxide and its hydrate, potassium carbonate and its hydrate, sodium carbonate and its hydrate, lithium carbonate and its hydrate, calcium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate.
14. The self-heating agent according to claim 13, characterized in that: Based on the total weight of the alkaline electrolyte, the sum of the mass percentages of the potassium hydroxide and its hydrate and the sodium hydroxide and its hydrate is 80% to 100%, and the sum of the mass percentages of the sodium carbonate and its hydrate, potassium bicarbonate and its hydrate, sodium bicarbonate and its hydrate, lithium bicarbonate and its hydrate, and calcium bicarbonate and its hydrate is 0 to 20%.
15. A self-heating device, characterized in that: The method comprises the self-heating agent according to any one of claims 11 to 14.
16. The application method of the self-heating device according to claim 15, characterized in that: An alkaline electrolyte is brought into contact with the self-heating particles.